2020
DOI: 10.1038/s41598-020-62320-4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of bioactive ingredients impacts liver and adipose tissue transcriptomes in a porcine model of prepubertal early obesity

Abstract: Global prevalence of obesity has increased to epidemic proportions over the past 40 years, with childhood obesity reaching alarming rates. In this study, we determined changes in liver and adipose tissue transcriptomes of a porcine model for prepubertal early obesity induced by a high-calorie diet and supplemented with bioactive ingredients. A total of 43 nine-weeks-old animals distributed in four pens were fed with four different dietary treatments for 10 weeks: a conventional diet; a western-type diet; and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 80 publications
3
9
0
Order By: Relevance
“…infantis IM-1 ® is known to secrete short chain fatty acids (SCFA) to the culture medium. Studies have shown a higher production of butyric, lactic, acetic and valeric acids in the intestines of animals fed with this probiotic strain [17][18][19][20]30,31]. Although we did not analyze the composition of the cell-free supernatant, we speculate that the anti-inflammatory effects observed in this study were due to its SCFA content.…”
Section: Discussionmentioning
confidence: 63%
“…infantis IM-1 ® is known to secrete short chain fatty acids (SCFA) to the culture medium. Studies have shown a higher production of butyric, lactic, acetic and valeric acids in the intestines of animals fed with this probiotic strain [17][18][19][20]30,31]. Although we did not analyze the composition of the cell-free supernatant, we speculate that the anti-inflammatory effects observed in this study were due to its SCFA content.…”
Section: Discussionmentioning
confidence: 63%
“…Background calibration, normalization, and log2 transformation were performed on the GSE135830 and GSE127056 datasets using Limma in R. When multiple probes were used to identify the same gene, the average value was calculated to determine the expression level. According to previous studies on the transcriptomics of the diet‐induced obesity (DIO) animal models, the gene expression changes related to obesity are usually at a modest and even subtle level 14,15 . As previously described, a fold change (FC) above 1.5 (i.e., |log 2 FC| > 0.585) and p value < 0.05 were set as the criteria for identifying DEGs using the Limma package 14,15 …”
Section: Methodsmentioning
confidence: 99%
“…According to previous studies on the transcriptomics of the diet‐induced obesity (DIO) animal models, the gene expression changes related to obesity are usually at a modest and even subtle level. 14 , 15 As previously described, a fold change (FC) above 1.5 (i.e., |log 2 FC| > 0.585) and p value < 0.05 were set as the criteria for identifying DEGs using the Limma package. 14 , 15 …”
Section: Methodsmentioning
confidence: 99%
“…al. [147] evaluated the liver and adipose tissue (visceral and subcutaneous) transcriptome of 20 pigs submitted to four dietary treatments (conventional diet; a Western diet; and a Western diet containing Bifidobacterium breve and hydrolysate, either with or without the addition of n-3) for 10 weeks. Differential expression gene analysis concluded an increase in cholesterogenesis, lipogenesis, and inflammatory processes in animals on the westerntype diet.…”
Section: Nutrigenomicsmentioning
confidence: 99%